SILEK TUO DI NAGARI GUNUANG KELURAHAN EKOR LUBUK KECAMATAN PADANG PANJANG TIMUR PROVINSI SUMATERA BARAT (Analisis Interaksionisme Simbolik George Herbert Mead) - Wardhana, M. Fhajar Vierta; Rosaliza, Mita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Abstract This study aims to analyze silek tuo Gunuang by using Herbert Mead's symbolic interascionism theory. This study uses descriptive qualitative with purposive sampling technique. The researcher interviewed as many as 5 informants consisting of 1 traditional leaders, trainers, players, as well as community leaders who understood about silek tuo Gunuang. The results showed that historically there were no people who knew when and who introduced silek tuo Gunuang in the past. It was the only martial arts school that was not shown for public and it was purely for martial arts. Kubu Gadang tourism village has a silek lanyah icon as a form of modification or takes a method from Silek Tuo Gunuang which is used for performance art. All the terms and elements relating to silek tuo gunuang and silek lanyah contain very positive historical meanings from the ancestral values of the past in the local area. Moreover, Silek Tuo Gunuang has functions including martial functions, social functions, and religious functions. Meanwhile silek lanyah has economic functions, entertainment functions, and social functions. Keywords: Silek Tuo, Simbolic Meaning, Nagari Gunuang